Biocompatible blood pool MRI contrast agents based on hyaluronan - Zhu, Wenlian (2010)
Biocompatible gadolinium blood pool contrast agents based on a biopolymer, hyaluronan, were investigated for magnetic resonance angiography application. Hyaluronan, a non-sulfated linear glucosaminoglycan composed of 2000–25,000 repeating disaccharide subunits of D-glucuronic acid and N-acetylglucosamine with molecular weight up to 20 MDa, is a major component of the extracellular matrix. Two gadolinium contrast agents based on 16 and 74 kDa hyaluronan were synthesized, both with R(1) relaxivity around 5 mM(−1) s(−1) per gadolinium at 9.4 T at 25°C. These two hyaluronan based agents show significant enhancement of the vasculature for an extended period of time. Initial excretion was primarily through the renal system. Later uptake was observed in the stomach and lower gastrointestinal tract. Macromolecular hyaluronan-based gadolinium agents have a high clinical translation potential as hyaluronan is already approved by FDA for a variety of medical applications.